Profile of Urticaria and Angioedema Patients at Dr. Moewardi General Hospital Surakarta, Indonesia - Dewi, Ayu Kusuma; Muhammad Eko Irawanto; Stella Gracia Octarica; Shelly Lavenia Sambodo; Rahmat Firdaus Dwi Utama; Sugih Primas Adjie (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Urticaria is a heterogeneous inflammatory skin disease that results from the activation and degranulation of cutaneous mast cells, followed by the release of histamine and other mediators that cause sensory nerve activation, vasodilation, plasma extravasation, and recruitment of immune cells. The prevalence and incidence of urticaria and angioedema have been extensively studied worldwide, but there is still limited data in Indonesia, especially regarding the profile of urticaria and angioedema patients. The purpose of this study was to determine the profile of urticaria and angioedema patients at Dr. Moewardi General Hospital for the period January 1st, 2020 - December 31st, 2022. Methods: This study is a cross-sectional retrospective study with secondary data derived from medical records of urticaria and angioedema patients. Results: There were 152 patients with urticaria, most of whom were in the age group >60 years (20.39%), female with a male to female ratio of 1:1.92, and worked as housewives (17.76%) and students (16.45%). Most cases were diagnosed with urticaria (86.84%) with some patients having angioedema (13.16%). The most common comorbidities rhinoconjunctivitis (2.63%), atopic dermatitis (1.97%) and asthma (1.32%). The dominant symptoms were itching and bumps (100%). The main treatment received by patients was single AH1 (71.71%) followed by combination therapy of AH1 and systemic corticosteroids (14.47%), combination therapy of AH1 and topical corticosteroids (10.53%), and the rest received combination therapy of AH1, topical corticosteroids, and systemic corticosteroids (3.29%). The skin prick test was positive in 16 patients (35.56%), with the most common allergens found being peanut (37.5%), egg yolk (37.5%), and tomato (37.5%). Conclusion: The characteristics of urticaria patients were dominated by elderly patients, female gender, and working as housewives or not working. Patients were predominantly diagnosed with urticaria with the most common comorbidities being diabetes mellitus. The main treatment received was AH1 class drugs. The most common types of allergens identified were peanuts, egg yolks, and tomatoes.